2009
DOI: 10.1523/jneurosci.5277-08.2009
|View full text |Cite
|
Sign up to set email alerts
|

Working Memory-Related Hippocampal Deactivation Interferes with Long-Term Memory Formation

Abstract: Previous findings indicate that the hippocampus does not only play a role in long-term memory (LTM) encoding, but is important for working memory (WM) as well, in particular when multiple items are being processed. A recent study showed that maintenance of multiple items was associated with hippocampal activation (hippocampus-dependent WM), while maintenance of individual items induced hippocampal deactivations (hippocampus-independent WM). Here, we used two complimentary approaches to investigate whether WM-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
40
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 31 publications
5
40
0
Order By: Relevance
“…Recent WM neuroimaging studies haves indicated the involvement of the hippocampus during WM encoding, maintenance and, retrieval (e.g., Axmacher et al, 2009aAxmacher et al, , 2009bFletcher et al, 2003;Öztekin et al, 2009;Schon et al, 2009). Using intracranial EEG, Axmacher et al (2007) demonstrated reduced hippocampus/MTL gamma power during maintenance of a single item, but increased power during maintenance of multiple items; fMRI data concurred with their intracranial EEG recordings.…”
Section: Hippocampal Recruitment In Cwms and Tnwm Taskssupporting
confidence: 53%
See 2 more Smart Citations
“…Recent WM neuroimaging studies haves indicated the involvement of the hippocampus during WM encoding, maintenance and, retrieval (e.g., Axmacher et al, 2009aAxmacher et al, , 2009bFletcher et al, 2003;Öztekin et al, 2009;Schon et al, 2009). Using intracranial EEG, Axmacher et al (2007) demonstrated reduced hippocampus/MTL gamma power during maintenance of a single item, but increased power during maintenance of multiple items; fMRI data concurred with their intracranial EEG recordings.…”
Section: Hippocampal Recruitment In Cwms and Tnwm Taskssupporting
confidence: 53%
“…Consequently, hippocampal activity during complex arithmetic operations may signal a role for the hippocampus as part of a temporary WM storage buffer for items retrieved from LTM not currently in the focus of attention. Axmacher et al (2009aAxmacher et al ( , 2009b recently arrived at a similar conclusion and this idea is akin to Cowan's embedded processes model where items retrieved from LTM not currently in the focus reside in an activated, easily accessible state within LTM. Support for the hypothesis that the hippocampus is involved in the maintenance of items during a CWMS task to a greater extent than during a TNWM task came from our OSPAN N Arithmetic contrast.…”
Section: Hippocampal Recruitment In Cwms and Tnwm Tasksmentioning
confidence: 87%
See 1 more Smart Citation
“…Traditionally, the frontal lobes are recognized as responsible for the control of complex cognitive processes such . However, more recently, there has been strong evidence indicating the contribution of the medial temporal lobe to WM 24,25,26,27 . In a less robust manner, the inferior temporal lobe's role in WM has also been demonstrated…”
Section: Discussionmentioning
confidence: 99%
“…The hippocampus employs these quadruplet signals (cf. Figure 4) when the brain handles more than one task [16]. In computational analyses, PCOs (doublets and quadruplets) are represented by stable limit cycles of longer periods (complex periodic orbits) in the phase space of the relevant dynamical system.…”
Section: Simulationmentioning
confidence: 99%